Pengaruh Media terhadap Produksi Prodigiosin Isolat Bakteri Entomopatogen Serratia marcescens Asal Wereng Batang Cokelat - Ifa Manzila; Tri P. Priyatno; Rahminovita Herlis; Iman Rusmana; I Made Samudra; Yadi Suryadi (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Prodigiosin, the red pigment producedby the bacterium Serratia marcescens, is a secondarymetabolite of the family tripyrrole that has been widely usedas an antibiotic in the multifunction treatment ofantibacterial as well as antifungal. This study was aimed tostudy the effect of Luria-Bertani (LB) broth and nutrientbroth (NB) media suplemented with several concentrationsof FeSO4 and CaCO3 on the production and characteristic ofprodigiosin derived from S. marcescens. The study wasarranged in a completely randomized factorial design withfour replications. The LB and NB media were supplementedwith 0, 2.5, 5, and 10 mM CaCO3 and 0, 0.25, 0.5, and 1 mMFeSO4. Results showed a red pigment produced by S.marcescens when cultured on both LB and NB media. Redlikepigmentation was varied when supplemented withdifferent concentration of Fe2+ and Ca2+. The higher theconcentration of Fe2+, the more intense the red color,conversely, the higher the concentration of Ca2+, the lighterthe red color. The interaction was found between the mediaand concentrations of CaCO3 and FeSO4 on the productionof prodigiosin. The highest prodigiosin production wasobtained on NB media supplemented with FeSO4.Meanwhile, the addition of CaCO3 did not affect theprodigiosin production. An addition of 1 mM FeSO4 to LBand NB media produced crude prodigiosin of 486.0 mg/mland 489.0 mg/ml, respectively. Based on purification bycolumn chromatography using silica gel, the prodigiosinproduction on LB and NB media was 378 mg/ml and 450mg/ml, with the purity level of 77.8% and 92%, respectively.Detection of prodigiosin by thin-layer chromatography usingsilica gel showed the red pigment had Rf value of 0.83 andbioautography assay showed there was an antibacterialactivity against Xanthomanas oryzae pv. oryzae.